2015
DOI: 10.1002/adma.201502735
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structural Design of Conjugated Microporous Poly(Benzooxadiazole) Networks for Enhanced Photocatalytic Activity with Visible Light

Abstract: A simple structural design principle and band position alignment of conjugated microporous polymers for enhanced photocatalytic efficiency is presented. The valence and conduction band positions of the polymer networks can be fine-tuned by altering the substitution positions on the centered phenyl unit to match the required redox potential of the catalytic reactions under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
161
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 262 publications
(165 citation statements)
references
References 41 publications
3
161
0
1
Order By: Relevance
“…[28] Ar ecent study on CMPs demonstrated that the geometry design of the 3D polymer network structure played an crucial role in improving the photocatalytic efficiencies of the CMP photocatalysts. [29] Herein, we report am olecular design strategy used to finetune the VB and CB levels within as eries of conjugated microporousp oly(benzochalcogenadiazole) networks by altering the chalcogene moieties in the acceptor,t hat is, the benzochalcogenadiazole unit of the polymer backbone. We show that the Metal-free visible-light photocatalystso ffer ac lean, sustainable solution to many pressing environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Ar ecent study on CMPs demonstrated that the geometry design of the 3D polymer network structure played an crucial role in improving the photocatalytic efficiencies of the CMP photocatalysts. [29] Herein, we report am olecular design strategy used to finetune the VB and CB levels within as eries of conjugated microporousp oly(benzochalcogenadiazole) networks by altering the chalcogene moieties in the acceptor,t hat is, the benzochalcogenadiazole unit of the polymer backbone. We show that the Metal-free visible-light photocatalystso ffer ac lean, sustainable solution to many pressing environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover,w e show that regeneration of NAD + by the photocatalyst nanoparticles can oxidize am odel substrate, in conjunction with the enzymeg lycerol dehydrogenase. [10] This class of metal-free polymer photocatalyst has recently emerged as ap romising alternative to traditional metal-containing catalytic systems, as it has additional features such as high stabilitya nd reusability. [1] Synthetic biology uses artificially designed modules as systems that can reproduce simple cell-like activity and even mimic rudimentary cellular behavior.…”
mentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are highly ordered two-or three-dimensional crystalline polymers [16,17]. These materials specially attract the interest in the area of photochemical hydrogen generation due to high surface area and tuneable pore size, which are essential criteria for heterogeneous catalysis [18].…”
Section: Covalent Organic Frameworkmentioning
confidence: 99%